Adenomyomatous uterine polyp in a Miniature Pinscher: histologic, immunohistochemical, and clinical aspects - Nueangphuet, Phawut; Tanabe, Mika; Izzati, Uda Zahli; Fuke, Naoyuki; Hirai, Takuya; Yamaguchi, Ryoji (SAGE Publications, 2022)
A 14-y-old Miniature Pinscher bitch was admitted to a veterinary clinic because of inappetence and a distended abdomen; ultrasound examination revealed a fluid-filled uterus with a single 1-cm hyperechoic nodule in its lumen. Ovariohysterectomy was performed. Grossly, the uterine horns were distended irregularly and asymmetrically, and the uterine lumen contained 200–300 mL of brown watery fluid. A single white polypoid 0.9-cm diameter nodule was present at the site of the distended uterine horn and arose from the endometrium with a narrow stalk. Histologically, the polyp consisted of dense, smooth muscle fascicles admixed with glandular components; its surface was covered by simple cuboidal epithelium with areas of squamous metaplasia. The myomatous cells expressed the myogenic markers smooth muscle actin and desmin. We interpreted the mass as an adenomyomatous uterine polyp, which is a rare variant of an endometrial polyp.